Comparison of modern and conventional imaging techniques in establishing multiple myeloma‐related bone disease: a systematic review. (25th April 2013) - Regelink, Josien C.; Minnema, Monique C.; Terpos, Evangelos; Kamphuis, Marjolein H.; Raijmakers, Pieter G.; Pieters – van den Bos, Indra C.; Heggelman, Ben G. F.; Nievelstein, Rutger‐Jan; Otten, Rene. H. J.; van, Danielle; Zijlstra, Josee M.; Arens, Anne I. J.; et al.
Summary This systematic review of studies compared magnetic resonance imaging (MRI), 18F‐fluorodeoxyglucose positron emission tomography (FDG‐PET), FDG‐PET with computerized tomography (PET‐CT) and CT with whole body X‐Ray (WBXR) or (whole body) CT in order to provide evidence‐based diagnostic guidelines in multiple myeloma bone disease. A comprehensive search of 3 bibliographic databases was performed; methodological quality was assessed using Quality Assessment of Diagnostic Accuracy Studies (QUADAS) criteria (score 1–14). Data from 32 directly comparative studies were extracted. The mean QUADAS score was 7·1 (3–11), with quality hampered mainly by a poor description of selection and execution criteria. All index tests had a higher detection rate when compared to WBXR, with up to 80% more lesions detected by the newer imaging techniques; MRI (1·12–1·82) CT (1·04–1·33), PET (1·00–1·58) and PET‐CT (1·27–1·45). However, the modern imaging techniques detected fewer lesions in the skull and ribs. In a direct comparison CT and MRI performed equally with respect to detection rate and sensitivity. This systematic review supports the International Myeloma Working Group guidelines, which recommend that WBCT can replace WBXR. In our opinion, the equal performance of MRI also indicates that it is a valuable alternative. As lesions of the skull and ribs are underdiagnosed by modern imaging techniques we advise additional X‐rays of these regions. The consequences of this approach are discussed.